The influence of game-based learning on business literacy - Isti Rahayu; Gilang Fakhri Listyawan; Primanita Setyono; Noor Endah Cahyawati (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2022)
Game-based learning used in various learning areas, including business learning. MonsoonSIM is a game simulator employed in a business learning process. This study study aims to investigate the influence of game-based learning using MonsoonSIM on business literacy and its effect on entrepreneurial intention. The population in this study are the students in the Special Region of Yogyakarta. Convenience sampling was used to select the research sample with the criteria of having experience of running MonsoonSIM. This study was conducted in 2022 based on a questionnaire to 121 students. In the analysis, Partial Least Square (PLS) was used with the results of game-based learning having a positive influence on business literacy, and entrepreneurial motivation having a positive influence on entrepreneurial intention. However, this study has not succeeded in proving the influence of environmental factors and business literacy on entrepreneurial intention. The study findings are expected to be a recommendation for higher education to apply game as a model alternative of business learning for a digital generation as it has been proven to promote business literacy.